VISI NEGARA IDEAL MENURUT PLATO: SEBUAH ANALISIS FILSAFAT SOSIAL-POLITIK - Duarte, Efatha Filomeno Borromeu (Jurnal Nawala Politika, 2023)
Plato is one of the foremost philosophers in history and his thoughts on politics center around the idea of the Ideal State. This analysis delves into Plato's vision for the perfect state, beginning with his homeland and the ideal form society should take. Drawing from his personal experiences, Plato proposed a highly esteemed government system. This examination discovered a recurring theme in Plato's beliefs, where the ideal state he envisioned was built upon education and virtue, striving to create a just and happy community. The Platonic ideal state takes the form of an Aristocracy, a country led by a philosopher or someone who is a master of philosophy. Plato placed great importance on education in the ideal state, believing that it is through education that people become virtuous and capable of critical and systematic thinking. The key to happiness in society, according to Plato, lies in the cooperation between the ruling class, the military class, and the peasant class.